A scientific note on the comparison of PCR based quantification methods of Melissococcus plutonius in honey bees. Issue 2 (21st November 2020) - Nesvorna, Marta; Sopko, Bruno; Bodrinova, Miroslava; Zitek, Justyna; Markovic, Martin; Navratilova, Blanka; Hubert, Jan
Abstract : Melissococcus plutonius is the causative agent of European foulbrood of honey bee larvae ( Apis mellifera ). The early diagnosis of disease is necessary for its elimination. Previously, we found false-positive results for PCR detection of M. plutonius in honey bee workers by qPCR. Here we report the comparison of PCR methods for quantification of M. plutonius in the bacteria spiked samples of honey bee workers and detection limits to eliminate false-positive results. We compare available primers of qPCR and PCR detection. The obtained detection limit was 10 2 copies of M. plutonius. The results of this comparison show conventional PCR detection using EFB_primers as a suitable method to confirm visual observation of European foulbrood using samples of honey bee workers. Based on our estimation, the numbers of M. plutonius should be quantified by copies of the Naþ/H þ 50 antiporter marker ( MP_primers ) in honey bee worker samples